Návrh newsletter systému pro elektronický obchod - Kundrát, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato práce se věnuje návrhu firemního newsletter systému pro rozesílání informačních a nabídkových emailů s nabídkou zboží zákazníkům. Systém bude určen pro velké a střední firmy, které provádějí obchodní činnost a nabízejí rozsáhlý sortiment zboží v internetových obchodech, kde vedou registrované zákazníky, kteří chtějí dostávat nabídkové emaily s aktuálními novinkami v obchodě.

The aim of this thesis is to describe a design of company newsletter system for sending information and e-mails with offers to customers. System is designed for large and medium companies which run a business and offer an extensive range of good in their online stores. In the database, which is connected with online stores, are registered many customers who want to receive emails with the latest news and offers in the store.
Design of Newsletter System for E-commerce Solution
Keywords: Newsletter systém; návrh newsletter systému; návrh informačního systému; systém pro rozesílání novinek; rozesílání emailů s novinkami.; Newsletter system; design of newsletter system; system for sending news; sending and creating newsletters; management of emails campaigns.